Tax Collection Reform: Challenges And Solutions For Improving Taxpayer Compliance - Susena , Karona Cahya; Damarsiwi , Eska Prima Monique; Putriani, Ririn (Utami Publisher, 2025)
Tax is an obligation that must be fulfilled by individuals or legal entities to the state without direct compensation, which is used for the benefit of the state for the welfare of the people. To manage taxes, a tax law system is needed that regulates the relationship between the government as collector and the people as tax payers. In Indonesia, tax collection faces various problems, such as weak regulations, lack of socialization, low tax awareness and knowledge, and economic problems. Apart from that, incomplete databases and suboptimal law enforcement are also challenges. The solution to overcome this problem is through tax reform which includes: improving tax regulations, increasing outreach to increase knowledge and awareness of taxpayers, evaluating policies, providing a more complete and secure database, and more firm and consistent law enforcement. In addition, tax collection must be carried out fairly, based on law, without disrupting the economy, efficiently and with a simple system.